Distribution of Large and Small Dorsal Root Ganglion Neurons in Common Marmosets - Kudo, Moeko; Wupuer, Sidikejiang; Kubota, Shinji; Seki, Kazuhiko (Frontiers in Systems Neuroscience, 2021)
The aim of this study was to elucidate the size and distribution of dorsal root ganglion (DRG) neurons in non-human primates and to compare them with those of rodent DRG neurons. By measuring the size of NeuN-, NF200-, and peripherin-positive DRG neurons in the lumbar spinal cord of rats and marmosets, we found that the cell size distribution pattern was comparable in both species, although DRG neurons in marmosets were larger than those of rodents. This is the first demonstration that DRG neurons in marmosets have a bimodal size distribution, which has been well established in rodents and humans.